Tree diversity and carbon storage cobenefits in tropical human‐dominated landscapes. Issue 2 (1st January 2020) - Osuri, Anand M.; Machado, Siddarth; Ratnam, Jayashree; Sankaran, Mahesh; Ayyappan, N.; Muthuramkumar, S.; Parthasarathy, N.; Pélissier, Raphaël; Ramesh, B. R.; DeFries, Ruth; Naeem, Shahid
Abstract: A lack of spatial congruence between carbon storage and biodiversity in intact forests suggests limited cobenefits of carbon‐focused policies for conserving tropical biodiversity. However, whether the same applies in tropical human‐dominated landscapes (HDLs) is unclear. In India's Western Ghats Biodiversity Hotspot, we found that while HDL forests harbor lower tree diversity and aboveground carbon stocks than relatively intact forests, positive diversity–carbon correlations are more prevalent in HDLs. This is because anthropogenic drivers of species loss in HDLs consistently reduce carbon storing biomass volume (lower basal area), and biomass per unit volume (fewer hardwood trees). We further show, using a meta‐analysis spanning multiple regions, that these patterns apply to tropical HDLs more generally. Thus, while complementary strategies are needed for securing the irreplaceable biodiversity and carbon values of intact forests, ubiquitous tropical HDLs might hold greater potential for synergizing biodiversity conservation and climate change mitigation.